MicroRNA-8 promotes robust motor axon targeting by coordinate regulation of cell adhesion molecules during synapse development. - Lu, C.S.; Zhai, B.; Mauss, A.; Landgraf, M.; Gygi, S.; Van Vactor, D. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2014)
Neuronal connectivity and specificity rely upon precise coordinated deployment of multiple cell-surface and secreted molecules. MicroRNAs have tremendous potential for shaping neural circuitry by fine-tuning the spatio-temporal expression of key synaptic effector molecules. The highly conserved microRNA miR-8 is required during late stages of neuromuscular synapse development in Drosophila. However, its role in initial synapse formation was previously unknown. Detailed analysis of synaptogenesis in this system now reveals that miR-8 is required at the earliest stages of muscle target contact by RP3 motor axons. We find that the localization of multiple synaptic cell adhesion molecules (CAMs) is dependent on the expression of miR-8, suggesting that miR-8 regulates the initial assembly of synaptic sites. Using stable isotope labelling in vivo and comparative mass spectrometry, we find that miR-8 is required for normal expression of multiple proteins, including the CAMs Fasciclin III (FasIII) and Neuroglian (Nrg). Genetic analysis suggests that Nrg and FasIII collaborate downstream of miR-8 to promote accurate target recognition. Unlike the function of miR-8 at mature larval neuromuscular junctions, at the embryonic stage we find that miR-8 controls key effectors on both sides of the synapse. MiR-8 controls multiple stages of synapse formation through the coordinate regulation of both pre- and postsynaptic cell adhesion proteins.